2020
DOI: 10.1002/saj2.20039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil texture on nitrogen mineralization from organic fertilizers in four common southeastern soils

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…When NH4 containing fertilizers such as ammonium nitrate (NH4NO3) or ammonium sulfate (NH4SO4) or urea (CH4N2O) are applied to soil during different stages of crop growth [36], they are typically subjected to immediate NH3 volatilization. For instance, upon application, urea undergoes hydrolysis ensuing higher soil pH in the microsites of soil causing transformation of NH4 + to NH3 [37,38]. The greatest amount of NH3 is released through anthropogenic activities [39], which releases around 7.6 million kg ha −1 of NH3 emission is from crop and animal husbandry accounting for more than 90% of the total emission [40].…”
Section: Ammonia Volatilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…When NH4 containing fertilizers such as ammonium nitrate (NH4NO3) or ammonium sulfate (NH4SO4) or urea (CH4N2O) are applied to soil during different stages of crop growth [36], they are typically subjected to immediate NH3 volatilization. For instance, upon application, urea undergoes hydrolysis ensuing higher soil pH in the microsites of soil causing transformation of NH4 + to NH3 [37,38]. The greatest amount of NH3 is released through anthropogenic activities [39], which releases around 7.6 million kg ha −1 of NH3 emission is from crop and animal husbandry accounting for more than 90% of the total emission [40].…”
Section: Ammonia Volatilizationmentioning
confidence: 99%
“…+ to NH 3 [37,38]. The greatest amount of NH 3 is released through anthropogenic activities [39], which releases around 7.6 million kg ha −1 of NH 3 emission is from crop and animal husbandry accounting for more than 90% of the total emission [40].…”
Section: Ammonia Volatilizationmentioning
confidence: 99%
“…This process is influenced by edaphic and climatic factors and in fact it is favored in soils with high pH, but also with acidic or neutral pH in the case of urea [2]. The hydrolyzed urea in soil solution increases the pH and determines the reduction of the ammonium ion into ammonia [33][34][35]. Ninety percent (%) of ammonia emissions (7.6 million kg ha −1 ) come from animal husbandry which derives from the hydrolysis of urea contained in urine and feces [36].…”
Section: Volatilization Of Ammoniamentioning
confidence: 99%
“…Failure to coordinate the timing of N release from organic fertilizers with the nutritional demands of crops may result in N loss and reduced productivity. Thus, it is important to accurately predict N mineralization rates from organic fertilizers and evaluate what factors may impact mineralization [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Organic fertilizers differ widely in physiochemical characteristics, and N mineralization rates can vary depending on these physiochemical properties. Total particle size, total N concentration, initial inorganic N levels and carbon to nitrogen (C:N) ratio can all affect the N mineralization of organic fertilizers [5][6][7][8][9][10]. In vitro incubation and field-based studies have shown that net N mineralization (Net N min ) among different organic fertilizers can vary between 20% to 93% of the total N applied [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%